2010
DOI: 10.1159/000317069
|View full text |Cite
|
Sign up to set email alerts
|

Level of Albuminuria and Risk of Stroke: Systematic Review and Meta-Analysis

Abstract: Background: Gross albuminuria is associated with increased stroke risk, but it is unclear whether stroke incidence varies by level of albuminuria. We meta-analyzed prospective cohort studies to investigate the impact of various albuminuria levels and continuous urinary albumin excretion (UAE) change on stroke risk. Methods: Systematic search for studies reporting quantitative estimates of the multivariate-adjusted relative risk (RR) and 95% CI for stroke risk associated with microalbuminuria (UAE 30–300 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
1
30
0
6
Order By: Relevance
“…Our study extends this finding to cerebrovascular disease and suggests that albuminuria can be used to predict the risk of stroke in individuals with known CKD. Prior studies have found an association of albuminuria with incident stroke in the general population 2326 , but this is the first study to assess the association of renal biomarkers with stroke risk specifically in individuals with CKD. Our study bolsters these earlier reports in a diverse sample of patients with CKD from a variety of etiologies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study extends this finding to cerebrovascular disease and suggests that albuminuria can be used to predict the risk of stroke in individuals with known CKD. Prior studies have found an association of albuminuria with incident stroke in the general population 2326 , but this is the first study to assess the association of renal biomarkers with stroke risk specifically in individuals with CKD. Our study bolsters these earlier reports in a diverse sample of patients with CKD from a variety of etiologies.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of stroke in our population is similar to that reported in other studies of stroke in patients with kidney dysfunction. 23 Medical history and medication use were self-reported by participants. Medication indication, compliance and/or effectiveness were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary albumin excretion (UAE) has been strongly linked to cardiovascular disease in persons with or without diabetes mellitus (Lee, Saver, Chang, & Ovbiagele, 2010). Moreover microalbuminuria, a marker of endothelial dysfunction, might be associated with pathophysiologic processes leading to cardiovascular diseases in patients with type 2 diabetes (Abdelhafiz, Ahmed, & El Nahas, 2011;Turkmen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MA is more prevalent in patients with increased risk of vascular events (e.g., diabetics and patients with hypertension) [3]. It predicts cardiovascular events and all-cause mortality in the general population and is a plausible risk factor for ischemic stroke [3].…”
mentioning
confidence: 99%
“…It predicts cardiovascular events and all-cause mortality in the general population and is a plausible risk factor for ischemic stroke [3]. Furthermore, MA occurs transiently in acute diseases with different etiologies and predicts greater short-and long-term mortality in stroke patients [4].…”
mentioning
confidence: 99%